Perceptions of administrative staff on career advancement realities at a South African university - Erasmus, Barney (Array, 2020)
The necessary training and development to equip staff to fill critical positions accounts for a substantial percentage of the annual budget of universities. This article reports on perceptions on career advancement among administrative staff at a South African university. This study extends the existing body of knowledge concerning the barriers to career advancement at universities. Qualitative research approach was adopted, with the sample consisting of 14 middle-ranking members of the administrative staff, who had been identified for possible senior management posts. Empirical results identified barriers which limit career advancement, namely that there has been a shift from a collegial to a managerial governance model; and that a perceived silo mentality has led to increasing politicisation of the workplace. Furthermore, a lack of managerial skill means that training opportunities and departmental goals are not well communicated to staff members; and inadequate career guidance, retention strategies and opportunities for promotion are all responsible for reducing prospects of career advancement. However, the participants indicated that they had not lost hope and would continue to perform to the best of their ability and even go beyond what was expected of them. Managers should, however, not lose sight of the possibility that morale and productivity will suffer, if talented employees become dissatisfied, and that future leaders may resign, with a consequent failure to achieve departmental goals. The results of this study may serve as a wake-up call to university management: strategies aimed at the retention of administrative staff and at promotion policies need to be revised because the staff that make up this cohort perform essential university services.